Emissão luminescente no titanato de cálcio dopado com íons de terras-raras - Pereira, S. C.; Paranhos, M. M.; Eduardo, A. C.; Santos, M. A. B.; Li, M. S.; Longo, E. [UNESP]; Motta, F. V.; Figueiredo, A. T. De (Associação Brasileira de Cerâmica, 2014)
Through the polymeric precursor method were synthesized samples Ca0.98Sr0.01X0.01TiO3 (X= Eu3+, Sm3+ and Pr3+), which under different heat treatments were obtained with levels of distinct structural order-disorder. The synthesized materials were characterized by X-ray diffraction, confirming the obtaining of ahomogeneous material with perovskite-type orthorhombic structure. This characterization allowed evaluating the average crystallite size of the samples that varies depending on the rare-earth ion. The results of photoluminescence emission confirmed the presence of this optical phenomenon at room temperature and its relationship to the level of order-disorder structural system. The photoluminescence emission is more intense in samples annealed at 500 ° C (independent on the dopant ion), the variation of the dopant influence on the emission intensity due to charge transfer between the host and emitting rare-earth ion, where the doped with Pr3+ ion has charge transfer more efficient and hence more intense emission in the photoluminescence. Another factor that favors the optical property of the samples is the charge compensation, as it contributes to the increase in structural disorder due to formation of Ca2+ vacancies.

Através do método dos precursores poliméricos foram sintetizadas amostras de Ca0,98Sr0,01X0,01TiO3 (X= Eu3+, Sm3+ ou Pr3+), que submetidas a diferentes tratamentos térmicos foram obtidas com níveis de ordem-desordem estrutural distintos. Os materiais sintetizados foram caracterizados por difração de raios X, confirmando a obtenção de um material homogêneo com estrutura perovsquita do tipo ortorrômbica. Essa caracterização permitiu ainda calcular o tamanho médio de cristalito das amostras, que varia em função do íon terra-rara presente. Os resultados da emissão fotoluminescente confirmaram a presença desse fenômeno óptico à temperatura ambiente e sua relação com o nível de ordem-desordem estrutural do sistema. A emissão fotoluminescente mais intensa ocorre nas amostras tratadas termicamente a 500 °C (independente do íon dopante), a variação do dopante influencia na intensidade da emissão devido à transferência de carga entre a matriz hospedeira e o íon terra-rara emissor, onde a amostra dopada com íon Pr3+ apresenta transferência de carga mais eficiente e consequentemente maior intensidade na emissão fotoluminescente. Outro fator que favorece a propriedade óptica das amostras é a compensação de carga, pois contribui para o aumento da desordem estrutural devido à formação de vacâncias do íon Ca2+.
Luminescent emission in calcium titanate doped with rare-earth ions
Keywords: perovsquita; titanato de cálcio; terras-raras; fotoluminescência; perovskite; calcium titanate; rare-earth; photoluminescence